2018
DOI: 10.1093/jas/sky037
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A pretreatment protects NO-induced bovine mammary epithelial cells from oxidative stress by modulating Nrf2 and NF-κB signaling pathways

Abstract: It is known that physiological overproduction of nitric oxide (NO) contributes to oxidative stress and inflammation. Our published studies indicated that vitamin A (VA) reduces NO-induced oxidative stress in bovine mammary epithelial cells (BMECs) by increasing antioxidant enzyme activities. However, the precise mechanism is unclear. The present study was conducted to examine the protective effects of VA on NO-induced damage to BMECs in vitro using diethylenetriamine nitric oxide (DETA-NO) as the NO donor and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…The Nrf2 pathway is stimulated by electrophiles and oxidants through the modification of critical cysteine thiols of Keap1 and/or phosphorylation of Nrf2, and the subsequently enhanced expression of antioxidant enzymes is achieved from the releasing of Nrf2 from Keap1 and translocating to the nucleus [ 31 ]. In the current study, protein expressions of both Nrf2 and Keap1 decreased after being treated with LPS, which was consistent with previous studies using different doses of pro-oxidants [ 7 , 20 , 32 ]. In contrast, the supplementation of DAE improved the expression of Nrf2 but declined expression of Keap1 at the DAE concentration of 50 μg/mL, which indicated that DAE induced the releasing of Nrf2 from Keap1.…”
Section: Discussionsupporting
confidence: 93%
“…The Nrf2 pathway is stimulated by electrophiles and oxidants through the modification of critical cysteine thiols of Keap1 and/or phosphorylation of Nrf2, and the subsequently enhanced expression of antioxidant enzymes is achieved from the releasing of Nrf2 from Keap1 and translocating to the nucleus [ 31 ]. In the current study, protein expressions of both Nrf2 and Keap1 decreased after being treated with LPS, which was consistent with previous studies using different doses of pro-oxidants [ 7 , 20 , 32 ]. In contrast, the supplementation of DAE improved the expression of Nrf2 but declined expression of Keap1 at the DAE concentration of 50 μg/mL, which indicated that DAE induced the releasing of Nrf2 from Keap1.…”
Section: Discussionsupporting
confidence: 93%
“…Previously, down-regulation of COX-2 by moringa extract was observed in other cell lines such as RAW 264.7 [41,42] and MCF-7 cells [43], in agreement with our data. Furthermore, the expression of COX-2 was regulated via NF-κB pathway in numerous studies using bovine mammary cells [3,20,24,44].…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is a heterodimer composed of p65 and p50 subunits [2,44]. Under normal circumstances, NF-κB heterodimer stays in the cytoplasm in an inactive form binding with an inhibitor of kappa-B alpha (IκBα).…”
Section: Discussionmentioning
confidence: 99%
“…Like CYP24A1, the induction of CYP26A1 is significantly reduced by LPS (Zolfaghari et al, 2007). Given the ability of AT-RA to protect bovine cells from oxidative stress and to potentiate the LPS-induced inflammatory cascade, preventing the induction of CYP26A1 may serve as a protective mechanism by prolonging the activity of AT-RA during infection (Shi et al, 2018;Xu et al, 2019).…”
Section: Vitamin a Degradationmentioning
confidence: 99%